OVERWEIGHT IN SCHOOLCHILDREN AND ASSOCIATION WITH PHYSICAL ACTIVITY AND PARENTAL HABITS - Palmeiro,Elena Sierra (2019)
ABSTRACT Introduction: Excess weight in childhood and adolescence is an important health problem that tends to persist in adulthood. Among the causes of this increase there appears to be a consensus on emphasizing physical activity as an excellent strategy to achieve better weight control, and on considering some models of parental practices essential for the acquisition of healthy habits in young people. Objective: To study the role of physical activity (undertaken by children and their parents) in the prevalence of overweight in Spanish schoolchildren. Methods: We studied 1687 schoolchildren aged between 13 and 17 years and 2335 mothers and fathers. The body mass index (BMI) of each child was calculated and information was collected on the physical activity level of the children and the parental physical activity level and BMI. Results: The schoolchildren analyzed have a higher prevalence of excess weight than the national average, significantly associated with age, sex, and excess weight of the mother, showing no significant association with the level of physical activity, but instead with the parental level of physical activity. Discussion: As predictive variables for excess weight in schoolchildren we found sex, age and excess weight of the mother. Conclusion: There is a prevalence of obesity and overweight in the sample of schoolchildren studied, and this is significantly associated with age rather than with physical activity. This prevalence is also significantly associated with the excess weight of the parents and with the level of physical activity of the father, which appears to confirm the influence of family characteristics and household physical activity in excess weight among schoolchildren. Level of Evidence I; Diagnostic studies - Investigating a diagnostic test.